In Vivo Confocal Microscopic Evaluation of Corneal Nerve Fibers and Dendritic Cells in Patients With Behçet’s Disease - Bitirgen, Gulfidan; Tinkir Kayitmazbatir, Emine; Satirtav, Gunhal; Malik, Rayaz A.; Ozkagnici, Ahmet (Frontiers in Neurology, 2018)
Central and peripheral nervous system involvement may occur during the course of Behçet’s disease (BD). In vivo corneal confocal microscopy (CCM) can detect corneal small fiber damage and immune cell density. The aim of this study was to assess central corneal sensitivity, corneal subepithelial nerve plexus morphology and dendritic cell (DC) density in patients with BD. Forty-nine consecutive patients with BD and 30 healthy control subjects were included in this cross-sectional study conducted at a tertiary referral university hospital. Central corneal sensitivity was measured using the contact corneal esthesiometer (Cochet-Bonnet; Luneau, France). The laser scanning CCM (Heidelberg, Germany) was used to quantify corneal nerve fiber density (NFD), nerve branch density (NBD), nerve fiber length (NFL) and DC density. There was a significant reduction in NFD (P = 0.001) and NFL (P = 0.031) and an increase in DC density (P = 0.038) in patients with BD compared to healthy controls, whereas corneal sensitivity (P = 0.066) and NBD (P = 0.067) did not differ significantly. There was no difference in corneal sensitivity, corneal nerve parameters or DC density between BD patients with (n=18, [36.7%]) and without a previous history of uveitis (P > 0.05 for all). Disease duration (median [IQR], 6.5 [4.0 - 14.5] years) correlated with corneal sensitivity (ρ = -0.463; P = 0.001) and NFD (ρ = -0.304; P = 0.034) and corneal sensitivity correlated with NFD (ρ = 0.411; P = 0.003) and NFL (ρ = 0.295; P = 0.039) in patients with BD. CCM demonstrates corneal sub-basal nerve fiber loss and increased DC density, providing a non-invasive ophthalmic means to identify peripheral neuropathy and inflammation in patients with BD.